2017
DOI: 10.1589/jpts.29.1129
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of locomotive syndrome with health-related quality of life among patients with obstructive sleep apnea syndrome

Abstract: [Purpose] This study aimed to examine the prevalence of locomotive syndrome among patients with obstructive sleep apnea syndrome (OSAS) using the “loco-check” recently developed by the Japanese Orthopedic Association, and to compare health-related quality of life (HRQOL) among patients with and without locomotive syndrome. [Subjects and Methods] This cross-sectional study evaluated 1,195 outpatients with OSAS (1,030 males and 165 females). Locomotive syndrome was evaluated using the Japanese Orthopedic Associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…Según el estudio de Kataoka et al 14 realizado sobre pacientes con síndrome obstructivo de la apnea del sueño se observó una disminución de la calidad de vida en los pacientes sin SL. Además, se mostró que la calidad de vida en estos pacientes era independiente del SL.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Según el estudio de Kataoka et al 14 realizado sobre pacientes con síndrome obstructivo de la apnea del sueño se observó una disminución de la calidad de vida en los pacientes sin SL. Además, se mostró que la calidad de vida en estos pacientes era independiente del SL.…”
Section: Discussionunclassified
“…Un estudio realizado sobre pacientes con patología respiratoria mostró una alta prevalencia de SL, demostrando una disminución en la calidad de vida 14 . Sin embargo, son escasos los estudios realizados para evaluar la relación del SL, la calidad de vida y la funcionalidad en pacientes con EPOC.…”
unclassified
“…Poor sleep quality is a major health problem worldwide (1)(2)(3). In universities, poor sleep quality can effect student's ability to study and have a serious impact on their psychological and physical well-being (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…However, some other studies [ 17 , 18 , 19 ] have reported that BMI does not affect the continuation of CPAP therapy, and there remains no consensus. Although we have previously reported a high prevalence of locomotive syndrome (LS) in OSAS patients (approximately 50%) [ 20 ], we are under the impression that OSAS patients with LS are more likely to drop out of CPAP therapy in our clinical practice. Therefore, in this study, we hypothesized that LS may be one of the risk factors for CPAP therapy dropout; to assess this, we evaluate the dropout rates between patients with and without LS using a survival analysis.…”
Section: Introductionmentioning
confidence: 99%